(3GdUdI aj CNHGQ CFeI GdCfOdSs - (3GHf HTchGd , Nda Hf YHO Gdedc Hf eSYhO Hf HTchGd GdNRQLj GdCfUGQj, CHhGdbGSe,J (B578 (3g` s ((3CMeO Hf Ydi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi aWQ HbOQJg GdBfGe , haVd HYVge Ydi HYV ai GdEagGe s
(3BNQgG (B:s
(3GfJgi GdZQV GdPi bUOfGg MSH eG SCdfGg hfSCd Gddg GdcQje EjRGY GdTcQ Ydi eG ChdGg , hGdJhajb deG jMHg hjQVGg s
(3YdjgG SeGYGJ cKjQI HYVgG dGHf OMjI GdcdHi hGHf YeQ GdCfUGQi GdHdfSi hZjQgeGs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B311 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B105s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B93 s
Keywords: (3GdJGQjNs